Nurses' supervisors, learning options and organisational commitment: Australia, Brazil and England. (4th August 2014) - Brunetto, Yvonne; Shacklock, Kate; Teo, Stephen; Farr‐Wharton, Rod; Nelson, Silvia
Abstract : Aim: To examine the relationships between leader–member exchange (LMX), workplace learning options (teamwork, training and development), empowerment and organisational commitment, for nurses in Australia, England and Brazil. Background: The supervisor–employee relationship is fundamental to management theory and practice within the work context of Organisation for Economic Cooperation and Development (OECD) countries. Methods: Survey‐based, self‐report data were collected from 1350 nurses in 23 acute‐care hospitals during 2011. Results: Significant relationships were found between key Social Exchange Theory antecedents (LMX and teamwork) and outcomes (organisational commitment) for nurses in Australia and England, but not in Brazil. As expected, the path between teamwork and organisational commitment was significant in the three countries. Conclusions: The findings affirm the importance of LMX as a management tool affecting employee outcomes in OECD countries. In contrast, LMX cannot be assumed to play an important role within a context that operates a dual employment structure coupled with a culture accepting of 'Jeitinho' workplace relationships. Implications for nursing management: Informal workplace relationships – 'Jeitinho' (similar to the Chinese 'guanxi') may be worthy of examination within BRICS (Brazil, Russia, India, China and South Africa) countries such as Brazil.